2014
DOI: 10.21273/hortsci.49.6.812
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Substrate Salinity and Nutrient Levels on Physiological Response, Yield, and Fruit Quality of Habanero Pepper

Abstract: Although habanero peppers (Capsicum chinense, Jacq.) are highly appreciated as a result of their organoleptic and pungency properties, the crop faces edaphic stresses throughout Mexico. A study was conducted to determine how the photosynthetic parameters, vegetative growth, yield, and fruit quality of the plant change in response to suboptimal conditions in the substrate. Habanero plants were grown in an inert substrate (perlite) and exposed to increased salinity levels (4 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 38 publications
0
17
4
2
Order By: Relevance
“…However, the production of both the mycorrhized and control plants was depressed at 6 mS•cm −1 EC, as a consequence of plant adaptation to water stress through vegetative growth reduction [44]. As a confirmation of the importance of genotype and crop system on plant tolerance to salinity, different findings compared to our results arose from previous research: a production drop with higher than 2.5 mS•cm −1 nutrient solution EC, made of either balanced element composition or sodium chloride addition [45]; no negative effects of nutrient solution EC increase from 4 to 7 dS•m −1 [46].…”
Section: Plant Growth and Yieldcontrasting
confidence: 57%
“…However, the production of both the mycorrhized and control plants was depressed at 6 mS•cm −1 EC, as a consequence of plant adaptation to water stress through vegetative growth reduction [44]. As a confirmation of the importance of genotype and crop system on plant tolerance to salinity, different findings compared to our results arose from previous research: a production drop with higher than 2.5 mS•cm −1 nutrient solution EC, made of either balanced element composition or sodium chloride addition [45]; no negative effects of nutrient solution EC increase from 4 to 7 dS•m −1 [46].…”
Section: Plant Growth and Yieldcontrasting
confidence: 57%
“…Paranychianakis and Chartzoulakis [20] reported that salt accumulation in the root zone caused development of osmotic stress and disrupted cell ion homeostasis, thereby affecting total yield. However, Urrea-Lopez et al [21] did not find that habanero pepper fruit yield parameters were significantly affected by low photosynthetic activity associated with water salinity, probably because of the fertilizers used in their experiment.…”
Section: Discussionmentioning
confidence: 83%
“…In peppers, profile and content of polyphenols are mainly related to plant genotype [8], but the degree of maturity and soil composition may play an important role [9,10]. Soils are a complicated physical, chemical and biological system that strongly influences the growth, development and quality of plants, affecting the synthesis and accumulation of secondary metabolites [11].…”
Section: Introductionmentioning
confidence: 99%